Tren Riset Pendidikan Agama Islam pada Google Scholar: Sebuah Analisis Bibliometrik - Wijaya Kusumah, Mada; Kartika Herdiyanti, Meitha; Nur Rahma, Farida (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This research aims to identify prominent themes (research trends) in IRE found on Google Scholar. Employing a bibliometric approach, this study utilizes databases from Google Scholar, spanning the years 2021 to 2024, to examine patterns and developments in IRE research. The research follows a five-step methodology: keyword identification (